2014
DOI: 10.1007/s11219-014-9253-3
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing agile benefits and limitations in relation to practice usage

Abstract: Context. In recent years there has been significant shift from rigid development (RD) towards agile. However, it has also been spotted that agile methodologies are hardly ever followed in their pure form. Hybrid processes as combinations of RD and agile practices emerge. In addition, agile adoption has been reported to result in both: benefits and limitations.Objectives. This exploratory study (a) identifies development models based on RD and agile practice usage by practitioners; (b) identifies agile practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
(49 reference statements)
3
32
0
Order By: Relevance
“…We need to better understand why these practices are not investigated as intensively as the others. With new studies that show that some practices are declining in their adoption (Murphy et al, 2013;Solinski and Petersen, 2014), it is also worth investigating the reasons why practices, like TDD and pair programming, that appear to have a positive impact on quality are declining in their adoption.…”
Section: Implications For Researchmentioning
confidence: 99%
“…We need to better understand why these practices are not investigated as intensively as the others. With new studies that show that some practices are declining in their adoption (Murphy et al, 2013;Solinski and Petersen, 2014), it is also worth investigating the reasons why practices, like TDD and pair programming, that appear to have a positive impact on quality are declining in their adoption.…”
Section: Implications For Researchmentioning
confidence: 99%
“…The lack of agreement on what constitute an Agile or Lean practice is further demonstrated in the variation of practices included in Agile surveys. Solinski and Petersen identified that the number of Agile practices included in Agile surveys vary between 14 and 59 practices . Meanwhile, Rodriguez et al reported the use of 16 Agile practices and 14 Lean principles from an industry survey in Finland .…”
Section: Background and Related Workmentioning
confidence: 99%
“…Solinski and Petersen identified that the number of Agile practices included in Agile surveys vary between 14 and 59 practices. 50 Meanwhile, Rodriguez et al reported the use of 16 Agile practices and 14 Lean principles from an industry survey in Finland. 51 In our study, we included 26 practices provided by Petersen 12 and complement them with 2 practices reported by Williams,15 which are definition of done and informative workspace.…”
Section: Agile and Lean Practicesmentioning
confidence: 99%
“…About the agile Adam Solinski and Kai Petersen in [1] discussed what are the most significant/insignificant benefits or limitations of agile practical usage. They find companies are inclined to switch to more flexible, adjustable approaches, but the usage of agile such as pair-programming and continuous integration with testing are commonly discarded.…”
Section: Related Workmentioning
confidence: 99%
“…ABSD is suitable for the big project where a higher level framework is needed. But like Adam Solinski and Kai Petersen in [1] said: SA is a good choice in certain domain where requirements are concise, stable, and seldom changed. However, in real world, there are almost no SA plans which are designed without revision.…”
Section: Introductionmentioning
confidence: 99%